2009
DOI: 10.1093/humrep/dep320
|View full text |Cite
|
Sign up to set email alerts
|

Increased risk of preterm births among women with uterine leiomyoma: a nationwide population-based study

Abstract: background: Using a 3-year nationwide population-based database, this study examines the risk of adverse pregnancy outcomes [lower birthweight, preterm gestation and babies small for gestational age (SGA)] in pregnant women with uterine leiomyoma.methods: This study linked two data sets: Taiwan's birth certificate registry and its National Health Insurance Research Data set. A total of 5627 mothers with uterine leiomyoma and 28 135 unaffected mothers were included for analysis. After adjusting for mother and i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
40
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(43 citation statements)
references
References 40 publications
3
40
0
Order By: Relevance
“…Preterm delivery was also more frequent in women with pregnancies complicated by large fibroids. Numerous studies have confirmed the association between uterine fibroids of any size and delivery at an earlier gestational age (6,(8)(9)(10)(11)(12). Although prior studies have not found an association between large uterine fibroids (>5 cm) and PTD (13,14), our findings suggest that large uterine fibroids >5 cm in diameter have a significant impact on earlier gestational age at delivery.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Preterm delivery was also more frequent in women with pregnancies complicated by large fibroids. Numerous studies have confirmed the association between uterine fibroids of any size and delivery at an earlier gestational age (6,(8)(9)(10)(11)(12). Although prior studies have not found an association between large uterine fibroids (>5 cm) and PTD (13,14), our findings suggest that large uterine fibroids >5 cm in diameter have a significant impact on earlier gestational age at delivery.…”
Section: Discussionsupporting
confidence: 55%
“…Moreover, findings may reflect an ascertainment bias because several retrospective studies identified women with fibroids on the basis of diagnosis codes or insurance records after delivery, rather than confirmation by antepartum obstetric ultrasonography (7). Nevertheless, evidence suggests that there is a trend toward delivery at an earlier gestational age in women with fibroids of any size (6,(8)(9)(10)(11)(12). Fibroids have also been reported to be associated with fetal malpresentation, intrauterine growth restriction, placenta previa, labor dystocia, placental abruption, delivery by cesarean section, retained placenta, and postpartum hemorrhage (PPH) (7).…”
mentioning
confidence: 99%
“…Birth outcomes showed controversial pattern: the previously reported somewhat higher rate of preterm birth was confirmed (e.g. [9]), but only in controls without CA and this increase was not significant. On the other hand, there was a larger mean birth weight of cases and controls born to mothers with LP, but it does not associate with a lower risk of low birthweight.…”
Section: Discussionmentioning
confidence: 72%
“…However, most studies of pregnancy complications and birth outcomes in uterine leiomyoma patients were composed of participants from only one hospital or clinic [4][5][6][7] and the results of population-based studies have been published only recently [8][9]. The objective of our study was the evaluation the possible association between maternal uterine leiomyoma in pregnancy (LP) and pregnancy complications, in addition adverse birth outcomes, particularly structural birth defects, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Another recent study using 3-years nationwide population-based database found an association between uterine fibroids and a small but significant increase in preterm labour and small for gestational age infants [89].…”
Section: Fibroids and Reproductive Functionsmentioning
confidence: 96%